Pengaruh Latihan Keseimbangan Terhadap Risiko Jatuh Pada Mahasiswa Olahraga - Wildayati; Sitti Fatimah Azzahra M; Mohammad Fandi Kurnia (PT Mediatama Zayna Indonesia, 2026)
Balance is a crucial component of physical fitness in determining the risk of falls. This study aims to determine the effect of balance training on the risk of falls in sports students at Makassar State University. The research design used was an experiment with a pre-test and post-test one group design. The study sample consisted of 30 students selected through purposive sampling technique with predetermined inclusion criteria. The instrument for measuring fall risk used the Timed Up and Go Test (TUG Test), while static balance was measured using the Single Leg Stance Test (SLST). The balance training program was given for eight weeks at a frequency of three times per week, including progressive proprioceptive training on various surfaces, core stabilization training, and dynamic balance training. Data analysis used a paired sample t-test with a significance level of alpha = 0.05. The results showed a significant effect of balance training on reducing the risk of falls (p = 0.000 < 0.05), with the mean TUG Test time decreasing from 11.43 seconds to 8.67 seconds and the mean SLST increasing from 18.24 seconds to 26.87 seconds. It was concluded that a structured and progressive balance training program significantly reduced the risk of falls and improved the balance abilities of sports students at Makassar State University.